Fighting in Vietnam the experiences of the U.S. soldier - Westheider, James E. 1956- (Stackpole military history series, 2011)
More than 3 million Americans served in the Vietnam War. By the war's end, 58,193 soldiers were killed, 61% of whom were aged 21 or under. More than 150,000 were wounded, and at least 21,000 were permanently disabled. In the post-war era, Americans struggled to absorb the lessons of the military intervention